KEDUDUKAN SAKSI INSTRUMENTAIR ATAS AKTA NOTARIS YANG MENIMBULKAN PERMASALAHAN DALAM PERKARA PERDATA - Dhaniaty, Marina (Program Pascasarjana Universitas Sunan Giri Surabaya, 2019)
The subject of the research is entitled Position of Witness Instrumentair on Notariy Deeds that Dispute and Inflict Problems, with the formulation of the problem How is the position of the instrumentair sanctioned in the notary deed and How is the scope of the instrumentair witness's responsibility in making a notary deed. Conclusions are obtained as follows: Sanctioned instrumentair in notary deed, to fulfill requirements as authentic deed, however the presence of witnesses of instrumentair is very necessary and is a requirement to be referred to as an authentic deed that has perfect proof power. In making the deed, since the notary read and signed the deed (verleijden), the instrumentair witness testified that it was true that the formalities determined by the law had been fulfilled, namely that before the parties signed, the deed had been read by the Notary to the party, then signed by the parties, everything is done before the witnesses of the instrumentair. The scope of the instrumentair witness's responsibility in making a notary deed can be explained that the instrumentair witness in making authentic deeds is limited to ratifying the deed as an authentic deed as desired by the nature and form of authentic deed, which is signed by the witness notary and instrumentair witness responsible for fulfilling the formalities determined by law, that the true viewer is present before a Notary and the identity of the viewer is in accordance with the description read by the Notary, that the deed before being signed by the parties is first read by the Notary to the viewers, and then signed by the parties concerned. it was carried out by a Notary and the parties before witnesses